Experimental study on vertical temperature distribution of symmetry axis of two identical rectangular pool fires with long sides parallel. (March 2021) - Wan, Huaxian; Yu, Longxing; Ji, Jie
Abstract: The axial temperature distribution of fire plume is an important subject in the field of fire research. While the gas temperature distribution induced by multiple fires is still not clear. This paper presents an experimental study on axial temperature distribution of two identical rectangular pool fires with long sides parallel. The pool aspect ratio and spacing were varied. Results showed that corresponding to different flame merging states including merging from the base, merging above the base and no merging, the axial temperature distribution appears three different change laws. Regarding the case of merging from the base as a large area fire, correlation of axial temperatures from various pool aspect ratios and spacings is proposed by introducing a virtual origin characterizing the effect of fire geometry. For the cases of merging above the base, taking the merging point as the boundary and determining the fire geometry and heat release rate of the upper assumed single fire, a piecewise function for the axial temperature distribution upon the merging point is established. The axial temperature characterizing the flame merging is further determined as 930 °C for two rectangular heptane pool fires, which can be used to judge whether the flames merge or not. Highlights: Burning of two rectangular pool fires with long sides parallel was conducted. The pool aspect ratio and spacing were changed. Temperature of symmetry axis of two fires showed three stages with rising spacing. Virtual origin describing fire geometry was introduced to correlate temperature. Correlations of axial temperatures for different merging stages were developed.